All-electrical driving and probing of dressed states in a single spin - Biu, HT; Wolf, C; Wang, Y; Haze, M; Ardavan, A; Heinrich, AJ; Phark, S-H (American Chemical Society, 2024)
The subnanometer distance between tip and sample in a scanning tunneling microscope (STM) enables the application of very large electric fields with a strength as high as ∼1 GV/m. This has allowed for efficient electrical driving of Rabi oscillations of a single spin on a surface at a moderate radiofrequency (RF) voltage on the order of tens of millivolts. Here, we demonstrate the creation of dressed states of a single electron spin localized in the STM tunnel junction by using resonant RF driving voltages. The read-out of these dressed states was achieved all electrically by a weakly coupled probe spin. Our work highlights the strength of the atomic-scale geometry inherent to the STM that facilitates the creation and control of dressed states, which are promising for the design of atomic scale quantum devices using individual spins on surfaces.